Meat quality of male and female Italian Padovana and Polverara slow-growing chicken breeds. Issue 1 (2nd January 2019) - Zotte, Antonella Dalle; Tasoniero, Giulia; Baldan, Gabriele; Cullere, Marco
Abstract: The study characterised and compared proximate composition and fatty acid (FA) profile of breast and leg meat of chickens belonging to Padovana and Polverara Italian local breeds. Birds were slaughtered at 183 days of age and four experimental groups were formed: Padovana males (PAD M), Padovana females (PAD F), Polverara males (POL M) and Polverara females (POL F). Proximate composition was assessed on 10 breasts and 10 legs per group, whereas FA profile and cholesterol content were assessed on six samples per cut per group. Breast meat proximate composition resulted in similarity between the two genotypes and sexes. Genotype did not affect breast FA profile except for C18:1 n -11, whereas females breast meat was richer in DHA ( p  < .05) and thus in n-3 ( p  < .05). Leg meat exhibited greater variability due to genotype and sex. Indeed, PAD chicken legs were richer in dry matter ( p  < .01), lipids ( p  < .01) and cholesterol ( p  < .01) than POL. It emerged that leg meat from PAD breed was characterised by a more desirable FA profile due to its higher UFA:SFA ( p  < .05) and lower n –6/ n –3 ( p  < .05) ratios. Despite exhibiting a lower PUFA:SFA ratio than males ( p  < .05), females exhibited a better n –6/ n –3 ratio ( p  < .01). The two genotypes and the two sexes possess peculiar nutritional quality. The aim of this study was to create economic interest around these local productions to assure their survival. Highlights: Padovana and Polverara are two rustic slow-growing chicken breeds which are farmed in the Veneto region of Italy. The goal of the present study is contributing to the creation of economic interest around local productions from Padovana and Polverara chickens. Creating an economic interest around Padovana and Polverara breeds would contribute to the preservation of local tradition and rural culture.